Evaluation of Probation for Drug Users by Probation Experts and Those Who Have Been Subjected to Probation Measures - Uzunyayla, Zuhal; Alkan, Nevzat (The Bulletin of Legal Medicine, 2024)
Objective: This study aimed to evaluate the effectiveness of the Probation, which is an alternative penal execution system for substance users with the Turkish Penal Code that entered into force in 2005, to identify the problems in its functioning and to offer solutions for the development. Methods: The study was conducted in four Probation Branch Directorates in Istanbul between October 2014 and June 2015. A questionnaire including sociodemographic data and opinions on the system was applied to 382 individuals (group 1) who were sentenced to “Treatment and Probation Measures” and 100 probation experts (group 2) working in the directorates. Results: It was determined that the group 1 sample was mostly single, male, adults, with secondary school education or below, and employed in an income-generating job, and that the most commonly used substance was cannabis, while the group 2 sample consisted of 4 different occupational groups, the majority of whom were sociologists, and that different occupational groups were doing the same job with the same job description, and that they had little experience in working with substance users. Conclusion: In both groups, it was determined that the system’s ability to raise awareness was not considered sufficient in general and rehabilitation activities were limited. It was concluded that developing tools to measure the effectiveness of the system in direct probation cases, evaluating the system objectively at regular intervals, increasing rehabilitation activities, and creating a structure in which non-governmental organizations, and academies are provided will make positive contributions to the Probation system.